Postoperative clinical nursing care pathway for patients with mucormycosis: An experience from a tertiary care hospital in Rajasthan, India - kalal, Nipin; Dr Suresh K Sharma,; Dr. kapil soni, (Nepal Journal of Epidemiology, 2021)
Background: The COVID-19 pandemic is a serious global health threat and it has numerous impacts on human life. India faced the problem of the second wave of COVID-19 and an unexpected new predicament in the form of mucormycosis has been added. The use of steroids drugs for long duration and comorbidity with COVID-19 infections are the risk factors of mucormycosis. It is important to understand the postoperative clinical pathway to assess and determine the policy and protocol, which help patients fasten their recovery, prevent further complications and readmission.  Methods: A cross‑sectional descriptive design was used to conduct the study. We adopted the validated Immediate Post-Operative Recovery Assessment (IPR-PA) Scale to assess the postoperative clinical nursing care pathway for patients with mucormycosis. Results: The current study shows that patients had highest score in the physiology clinical recovery domain (75.25%) and the lowest post-operative clinical recovery score in psycho-social domain (20.83%). There was a significant positive correlation was found between all the domains. The medication status domains found significantly associated with participants’ age (P=.021) and physiological domains has shown significant association with received oxygen therapy during hospitalization (P=.046).Conclusion: Postoperative clinical nursing care pathway was effective to determine the progress of a patient. It helps us to know the parameter of different domains namely being physiological, physical, psycho-social and medication status. Patients required psycho-social support due to the epidemic and fear from disease.